Deregulation of Malaysian Petroleum Industry:Searching for the Right Model - Wong, Zun Haur (2005)
In the last twenty years, economic liberalization has become a prevalent trend in world economy where the once state owned enterprises or regulated industries had undergone various forms of liberalization that include privatization and deregulation. The rapid advancement in technology, particularly in the areas of transportation and dissemination of information, has brought people closer and made them similar. This growing trend has resulted in what we now call globalization of the world. Globalization drives the greater political and economical integration between states but reduces the powers of individual state in regulating their own economy. Petroleum industry, like finance and agricultural industries, is traditionally regarded as critical to the national interest and hence historically being heavily regulated. However, this has changed after the end of cold war in 1980s. As the threats of national security as well as the threats of crude oil supply disruption were gradually removed, many countries took steps to deregulate their petroleum industry, especially its downstream sectors. United States (US) is one of the earliest countries that deregulated its retail gasoline market in 1981. Subsequently, many other developed countries like Japan, New Zealand, Australia, United Kingdom (U.K.), France, Germany, Italy and few other European countries had follow suit. Countries in Asia, like India, Thailand, South Korea, Philippine and Singapore have almost all deregulated their petroleum industries in the 1990s, despite some were actually forced into it during the Asian financial crisis in 1997/98. In Malaysia, the petroleum industry was spared from the wave of deregulation during the financial crisis. Presently, the industry is still regulated by the government mainly under the Petroleum Development Act (PDA) 1974 and its auxiliary Automatic Pricing Mechanism (APM). Under the existing regulatory framework, the government is responsible in fixing the prices of petroleum products and regularly adjusting the tax or subsidy element in these products to accommodate the changes in cost and to maintain the prices. The petroleum products regulated under the APM framework are Petrol RON 97, Petrol RON 95, Diesel and Liquefied Petroleum Gas (LPG). In tandem with the high crude oil prices in the last few years, Malaysian government had spent significant amount of petroleum subsidies to keep the fuel prices low. In year 2004, the government said it had spent a staggering 4.8 billion Malaysian Ringgit in petroleum subsidies, and expected to spend more if the oil prices remain high in the coming years. Deregulation and liberalization of the petroleum industry is an option the government could take to free itself from this heave financial burden. Nevertheless, like a two-edged sword, the regulatory change may also bring with it unfavorable effects like hyper-inflation, increase of business costs and worsening of other social-economic problems such as crimes and poverty. This dissertation attempts to explore the possibility of deregulating the petroleum industry in Malaysia as a mean to resolve the existing issues and provide greater efficiency in the industry. The research methodology of this paper is based on interviews with the senior officers from selected key stakeholders of the industry.